2007
DOI: 10.1021/nl0710452
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes in the Intact Organism:  Near-IR Imaging and Biocompatibility Studies in Drosophila

Abstract: The ability of near-infrared fluorescence imaging to detect single-walled carbon nanotubes (SWNTs) in organisms and biological tissues has been explored using Drosophila melanogaster (fruit flies). Drosophila larvae were raised on food containing ∼10 ppm of disaggregated SWNTs. Their viability and growth were not reduced by nanotube ingestion. Near-IR nanotube fluorescence was imaged from intact living larvae, and individual nanotubes in dissected tissue specimens were imaged, structurally identified, and coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 20 publications
(25 reference statements)
7
196
0
Order By: Relevance
“…Spectrofluorimetry has been used to quantitatively identify SWNTs in rabbits [87], cells [86], and fruit flies [109]. However, this approach detects only individually dispersed semiconducting SWNTs and cannot be used to detect MWNTs, metallic SWNTs, or bundles of SWNTs that contain metallic SWNTs.…”
Section: Methods Of Cnp Analysis In Other Matricesmentioning
confidence: 99%
“…Spectrofluorimetry has been used to quantitatively identify SWNTs in rabbits [87], cells [86], and fruit flies [109]. However, this approach detects only individually dispersed semiconducting SWNTs and cannot be used to detect MWNTs, metallic SWNTs, or bundles of SWNTs that contain metallic SWNTs.…”
Section: Methods Of Cnp Analysis In Other Matricesmentioning
confidence: 99%
“…For SWNTs, a highly sensitive and selective imaging microscopy technique is available based on NIRF microscopy [31]. This technique can detect single semiconductive SWNT particles in biological samples and has been used to examine the biodistribution of these CNMs in Drosophila melanogaster [32]. Extension of this technique to aquatic organisms and sediments should be straightforward and will provide a valuable tool for microspatial localization of SWNTs in solid environmental phases.…”
Section: Imaging Of Cnms In Sediments and Biotamentioning
confidence: 99%
“…1, pp. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]2012 # 2011 SETAC Printed in the USA DOI: 10.1002/etc.723 This paper evolved from discussions held at a SETAC-endorsed Technical Workshop held at Clemson University in August, 2010. The workshop was sponsored by the United States Environmental Protection Agency (U.S. EPA), Arcadis-US, and the Clemson University Institute of Environmental Toxicology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has also demonstrated that it is possible to achieve limited separation of exfoliated SWNTs according to (n,m) structure, 58,121,136 left-or right-handed chirality, 95 length, 137,138 and electronic character (i.e., metallic or semiconducting). [139][140][141][142][143][144][145] SWNT surfactants are classified in terms of their ionic character (i.e., anionic, cationic, or nonionic). Ionic surfactants have a positively or negatively charged head group that interacts with the solvent and a nonpolar tail that associates with the nanotube sidewall; SWNT aggregation is hindered by charge repulsion between the polar head groups that extend into the solvent.…”
Section: Motivationmentioning
confidence: 99%